MENTARJIH PENETAPAN NASAB ANAK ZINA KEPADA AYAH BIOLOGIS BERDASARKAN KONSEP ANAK DAN MAQSAD HIFZ AL-NASL - Solihul Aminal Ma'mun (Al-Maslahah : Jurnal Ilmu Syariah, 2020)
Nasab is a bloodline that binds human relations with the father up, children down and sideways. Preservation of nasab including part of the favors of God that has been given to his servant. Because nasab is the basis for protecting people from damage, intricacy and forgery. In the order of Islamic rules nasab child is given to his father. The indication is that a father in Islam is burdened with the responsibility to provide the fulfillment of clothing, food and shelter for his child, or in the general sense a father is obliged to protect, nurture and be a role model for his children. But what if there is a child who is not allowed to rage on his father as the opinion of the majority of Islamic scholars? namely a child born from the result of a relationship outside of marriage (adultery), where at the time of birth his mother had not had time to get married, despite the opinion of a minority of Islamic scholars who disagree with the opinion of the majority. Therefore, the author tries to explain to give priority (tarjih) to the opinion of the minority from the opinion of the majority who have given biological father the opportunity to determine the child he confesses to himself, even without marrying his mother. Because of minority opinion, when viewed in terms of the broad meaning of maqsad hifz al-nasl is very close. This study is a library research and uses a qualitative-inductive approach or in Arabic called tahlili-istiqrai method with theories that are part of the ushul fiqh methodology. The results that the authors take from this study are with al-tarjih baina qaulauini by looking at the most propositions from both opinions. Among them by looking at the perspective of the concept of children and maqsad hifz al-nasl.